Multiscale optimal design and fabrication of laminated composites. (15th November 2019) - Boddeti, Narasimha; Rosen, David W.; Maute, Kurt; Dunn, Martin L.
Abstract: We present a general framework that digitally integrates the workflow for optimal design and fabrication of novel multiscale laminated fiber-based composites with spatially varying microstructure in each lamina of a flat or curved laminate. Given a design problem, our framework consists of three key components: 1) Design automation, 2) Material compilation, and 3) Digital fabrication . Design automation involves efficient simultaneous synthesis of optimal macroscale topology and spatially varying fibrous microstructure in a laminated composite, whereas digital fabrication comprises manufacture of the optimal structure. Material compilation is an intermediate process that translates the multiscale results of the design automation step to a digitally manufacturable arrangement of matrix and fibers within each layer of a laminate. These components constitute a digital thread and can be initialized by any method or process of choice. In this paper, we develop a multiscale topology optimization approach for design automation, new computational geometry algorithms for material compilation, and voxel-based material jetting for digital fabrication. We demonstrate and experimentally validate the extensive capabilities of our framework with various plate and shell structures that have potential applications in architecture, aerospace and soft robotics.